2017
DOI: 10.1177/1471301217737872
|View full text |Cite
|
Sign up to set email alerts
|

Memory Keeper: A prototype digital application to improve engagement with people with dementia in long-term care (innovative practice)

Abstract: People with dementia living in long-term care commonly experience loneliness and lack of meaningful activity. Memory Keeper is a prototype digital application that presents personalised prompts to stimulate reminiscences and meaningful engagement with formal and informal carers. A trial involving three persons with dementia in long-term care and seven family and staff members revealed no negative responses to the device or application. Family members said it was valuable in improving the quality of engagement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 14 publications
2
67
0
1
Order By: Relevance
“…The interaction support seemed especially bene cial for spouses that felt burdened by faltered communication due to the progressive nature of dementia. The tablet-based social interactions seemed to result in higher amounts of communicative actions and increased frequency and duration of visits [19,22]. Family members reported that the convenient tablet-technology provided more enjoyable and meaningful interaction, which supported their relationship [22].…”
Section: Facilitating Interactionsmentioning
confidence: 97%
See 2 more Smart Citations
“…The interaction support seemed especially bene cial for spouses that felt burdened by faltered communication due to the progressive nature of dementia. The tablet-based social interactions seemed to result in higher amounts of communicative actions and increased frequency and duration of visits [19,22]. Family members reported that the convenient tablet-technology provided more enjoyable and meaningful interaction, which supported their relationship [22].…”
Section: Facilitating Interactionsmentioning
confidence: 97%
“…In addition to reported effects on wellbeing, reminiscence can potentially increase interaction in longterm care (LTC) facilities, ultimately building relationships and increasing connections [17]. When using tablets as a third-party in social interactions, the intuitive design and variety of applications can offer both personalized and generic content in a manner that eases the introduction and maintaining of conversation topics, thus enhancing the social interaction [13][14][15][19][20][21][22][23][24][25][26].…”
Section: Tablet Computersmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose pictures that would be familiar to a broad range of cultures, not childish, but that includes pictures of children, and all the generations. These intergenerational and family images with clear unambiguous emotional expressions were chosen to make it easier for PwD to recognize the emotions of the characters and empathize, sympathize and interact with them (McAllister et al, 2020), and give a feeling of warmth and belonging (see Figure 2). Nature scenes were included as well, to elicit emotions of calmness and enjoyment (Gamble et al, 2014;Thake et al, 2017).…”
Section: Goals and General Designmentioning
confidence: 99%
“…The articles by McAllister et al (2017), Ferry et al (2018), and Ryan et al (2018) reported the results of digital apps that support reminiscences and meaningful engagement with carers. Finally, the article by Gibson et al (2016) is a scoping review that explored the provision of assistive technology products available for people with dementia.…”
mentioning
confidence: 99%